Desenvolvimento de equipamento multifuncional portátil de baixo custo para determinações fotométricas, turbidimétricas, nefelométricas e fluorimétricas - Reis, Rodrigo Alexandre [UNESP] (2014)
A new portable, low cost and multifunctional equipment comprising four analytical techniques (photometry, turbidimetry, nephelometry and fluorimetry) in one single device was developed The main components of the developed device are light emitting diode (LED) as radiation source, light-dependent resistor (LDR) as photodetector, digital multimeter as reading device, and a black plastic container. The performance of the device was checked by determining phosphorus in fertilizer (photometry), sulfur in fertilizer (turbidimetry), sulfur in vegetable samples (nephelometry) and quinine in tonic water (fluorimetry). All determinations were also made in commercial equipments for comparison purposes. The phosphovanadomolibdate method was employed for phosphorus determination within the 0.07 – 6.52 mg L-1 concentration range ((r= 0.9944), and the detection limit was 0.06 mg L-1. The precipitation of barium sulfate was employed for turbidimetric and nephelometric determination of sulfate. For the turbidimetric technique, the calibration range was in the 2.5 - 100 mg L-1 (r= 0.9982), and the detection limit was 0.23 mg L-1. For nephelometry, calibration within 0.2 – 1.8 mg L-1 (r= 0.9948) resulted in detection limit of 0.10 mg L-1. The fluorimetric determination of quinine in the 0.16 – 8.0 mg L-1 linear working range (r= 0.9982) resulted in 0.011 mg L-1 detection limit. Results found by the proposed device were in agreement with those obtained by commercial equipments at 95% confidence level. Standard reference materials were also analyzed, and results for P and S were in agreement with certified values. Besides analytical capabilities, the proposed device may be useful for teaching. The learning goals of some optical techniques may be easier using easy-to-make instruments.